Oxidative carbonylation of N-protected indoles by Rh(iii)-zeolites. Issue 16 (7th February 2023) - Van Minnebruggen, Sam; Marquez, Carlos; Krasniqi, Besir; Janssens, Kwinten; Van Velthoven, Niels; Vercammen, Jannick; De Soete, Benoit; Bugaev, Aram; De Vos, Dirk
Abstract : The oxidative carbonylation of N -protected indoles was investigated to directly synthesize indole-3-carboxylic acids. Abstract : The oxidative carbonylation of N -protected indoles was investigated to directly synthesize indole-3-carboxylic acids. Using Rh(iii )-zeolites as heterogeneous catalysts, the single-site Rh-species reach unprecedented activities (>100 turnovers), while the metal is readily recovered after reaction. X-ray absorption spectroscopy (XAS) provided evidence for site-isolation of Rh(iii ) species on the zeolite.